Features of business models in the market of payment services - S. V. Krivoruchko; V. A. Lopatin (Стратегические решения и риск-менеджмент)
Features of business models of participants of the market of retail payment services are considered. An approach based on the allocation of nine elements of the business model is used: consumer segments, value propositions, sales channels, customer relationships, revenue streams, key resources, key activities, key partners, cost structure